THE EFFECT OF INFORMATION AND TECHNOLOGY (IT) BASED PARAGRAPH WRITING MATERIALS FOR STUDENTS' WRITING SKILLS IN PANDEMIC ERA - Sulistyahadi, Sulistyahadi; Hasbullah (LPSDI Bina Patria, 2023)
Nowadays almost technological facilities are owned by all students such as laptop or best HP multifunctional. The pandemic era forces human do all of the activities by using these media, this condition also forces the students and lecturer in the university to do teaching and learning process by using those media too. Mandating that the learning process begins to make technology as a learning medium that is able to create a conducive and wider atmosphere so that lecture learning is not limited by face to face activities and printed handbook but can use technology as a material development and learning process especially related to